Kaposi’s Sarcoma-Associated Herpesvirus Genome Replication, Partitioning, and Maintenance in Latency - Ohsaki, Eriko; Ueda, Keiji (Frontiers in Microbiology, 2012)
Kaposi’s sarcoma-associated herpesvirus (KSHV) is thought to be an oncogenic member of the γ-herpesvirus subfamily. The virus usually establishes latency upon infection as a default infection pattern. The viral genome replicates according to the host cell cycle by recruiting the host cellular replication machinery. Among the latently expressing viral factors, LANA seems to play pivotal roles in viral genome replication, partitioning, and maintenance. LANA binds with two LANA-binding sites (LBS1/2) within a terminal repeat sequence and is indispensable for viral genome replication in latency. The nuclear matrix region seems to be important as a replication site, since LANA as well as cellular replication factors accumulate there and recruit the viral replication origin in latency (ori-P) by its binding activity to LBS. KSHV ori-P consists of LBS followed by a 32 bp GC-rich segment (32GC). Although it has been reported that LANA recruits cellular pre-replication complexes (pre-RC) such as origin recognition complexes (ORCs) to the ori-P through its interaction with ORCs, this mechanism does not account completely for the requirement of the 32GC. On the other hand, there are few reports about the partitioning and maintenance of the viral genome. It has been reported that LANA is present at the CEN through its interaction with CENP-F, suggesting that KSHV genome segregation might affect the cellular mitotic checkpoint. Furthermore, LANA interacts with many kinds of chromosomal proteins, including Brd2/RING3, histones such as H2A/H2B and also H1, and so on. No consensus, however, exists for KSHV genome partitioning and maintenance. By integrating the findings reported thus far on KSHV genome replication, partitioning, and maintenance in latency, we will summarize what we know now, discuss what questions remain to be answered, and determine what needs to be done next to understand the mechanisms underlying viral replication, partitioning, and maintenance.